Wearable Sensors and Robots Proceedings of International Conference on Wearable Sensors and Robots 2015 - Yang, Canjun; Virk, G. S.; Yang, Huayong (Lecture Notes in Electrical Engineering, 2017)
These proceedings present the latest information on regulations and standards for medical and non-medical devices, including wearable robots for gait training and support, design of exoskeletons for the elderly, innovations in assistive robotics, and analysis of human-machine interactions taking into account ergonomic considerations. The rapid development of key mechatronics technologies in recent years has shown that human living standards have significantly improved, and the International Conference on Wearable Sensor and Robot was held in Hangzhou, China from October 16 to 18, 2015, to present research mainly focused on personal-care robots and medical devices. The aim of the conference was to bring together academics, researchers, engineers and students from across the world to discuss state-of-the-art technologies related to various aspects of wearable sensors and robots. .